IMPROVING THE STUDENTS' VOCABULARY REPERTOIRE USING MODIFIED TOTAL PHYSICAL RESPONSE METHOD AT SDN KARANGJATI KALIJAMBE (AN ACTION RESEARCH) - Fithri, Shofa Anisa (2011)
This research aims to describe the students' ability of vocabulary repertoire using Total Physical Response method in SDN Karangjati Kalijambe. The result of the study is expected to contribute to the teaching learning of vocabulary especially in understanding meaning, pronounce and spell ability. The research paper is an action research in which the data are in the form of field note, interview script, and students' worksheet. The research was done from 4 October to 9 October 2010 in SDN Karangjati. The researcher takes 20 students as the subject of the research. The object of the research is English vocabulary repertoire in SDN Karangjati. The researcher gets the data from events, informants and document. While the techniques of collecting data are observation, interview, and test. The result of the research shows that the teaching vocabulary repertoire using modified Total Physical Response for the sixth year students of SDN Karangjati is successful. It can be seen from every cycle where the students were able in understanding meaning, pronounce and spell the words correctly. By seeing given such questions and instructions related to the material, they could have a good understanding about the material itself. The students' vocabulary repertoire is improved. It can be seen from the result of calculating the mean of pre-test and post-test. It shows the improving pre-test mean (55,5) to the post-test mean (72,1). The number of improvement is about 16,6 drawn from the subtraction of post-test with pre-test mean.